PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA (STUDI PADA DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU) - Rona Try Devi Pane; Jumiati Sasmita; Yusni Maulida (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of work motivation and work environment on employee performance through job satisfaction at the Pekanbaru City Environment and Hygiene Service. The research was conducted at the Department of Environment and Hygiene of Pekanbaru City.The data used consists of primary data and secondary data. Data were collected using a questionnaire given to employees. The population in this study were employees of DLHK Pekanbaru City, totaling 105 employees and with a sample of 105 employees. The analytical tool used is path analysis.The results of this study indicate (1) Work motivation has a positive and significant effect on employee job satisfaction (2) Work environment has a positive and significant effect on employee job satisfaction (3) Job satisfaction has a positive and significant effect on employee performance (4) Work motivation has a positive and significant effect on employee performance. significant effect on employee performance (5) work environment has a positive and significant effect on employee performance, (6) work motivation affects performance through employee job satisfaction, (7) work environment affects performance through employee job satisfaction